Alveolar macrophages in early stage COPD show functional deviations with properties of impaired immune activation - Baßler, Kevin; Fujii, Wataru; Kapellos, Theodore S.; Dudkin, Erika; Reusch, Nico; Horne, Ari; Reiz, Benedikt; Luecken, Malte D.; Osei-Sarpong, Collins; Warnat-Herresthal, Stefanie; Bonaguro, Lorenzo; Schulte-Schrepping, Jonas; et al. (Frontiers in Immunology, 2022)
Despite its high prevalence, the cellular and molecular mechanisms of chronic obstructive pulmonary disease (COPD) are far from being understood. Here, we determine disease-related changes in cellular and molecular compositions within the alveolar space and peripheral blood of a cohort of COPD patients and controls. Myeloid cells were the largest cellular compartment in the alveolar space with invading monocytes and proliferating macrophages elevated in COPD. Modeling cell-to-cell communication, signaling pathway usage, and transcription factor binding predicts TGF-β1 to be a major upstream regulator of transcriptional changes in alveolar macrophages of COPD patients. Functionally, macrophages in COPD showed reduced antigen presentation capacity, accumulation of cholesteryl ester, reduced cellular chemotaxis, and mitochondrial dysfunction, reminiscent of impaired immune activation.